(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT Metalanguage is language used to describe or analyze language itself. It's like a language that talks about language. It can be grammatical terms: noun, verb, adjective, adverb, etc. Literary devices: metaphor, simile, personification, etc. Linguistic concepts: phoneme, morpheme, syntax, semantics, etc. Metalinguistic awareness, the ability to think about language as an object, plays a crucial role in developing strong reading skills.